PENERAPAN SISTEM INFORMASI GEOGRAFIS DALAM PEMANTAUAN PERUBAHAN LUASAN ANGROVE DI KECAMATAN JAWAI KABUPATEN SAMBAS SELAMA TAHUN 2013 - 2022 - Nurul Fatimah Yunita,; Muhammad Usman,; Dewi Merdekawati, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
This research aims to monitor changes in the area of mangrove vegetation using the Geographic Information System, or GIS, in the Jawai District area. The observation data used are Landsat 8 satellite images from 2013, 2016, 2019, and 2022. The results of the data analysis were obtained from 13 villages in Jawai District; only one village does not have mangrove vegetation, namely Dungun Laut Village. The vegetation area in this district in 2013, 2016, 2019, and 2022, respectively, was 812.91 ha, 913,813 ha, 1037,813 ha, and 1023,217 ha. The lowest vegetation area in 2013 was 27,244 ha, and the highest was 190,219 ha. In 2016, the lowest vegetation area was 2,784 ha, while the highest area reached 201,015 ha. 2019 showed the lowest vegetation area, namely 11,856 ha, with the lowest reaching 212,269 ha. The lowest area of mangrove vegetation in 2022 will be 19,112 ha, and the highest will reach 212,335 ha. Sentebang Village is a village with the lowest mangrove vegetation area compared to other villages. Meanwhile, the village with the highest area of mangrove vegetation is Sarang Burung Kolam.